Los grupos consonánticos /-n’r-/ y /-l’r-/ en el futuro : simple y en el condicional simple del castellano - Kispéter, Mónika (Acta Hispanica, 2009)
The aim of this article is the investigation of certain Spanish conjugated verb forms in future tense and in conditional mode. These forms during the Middle Age had more verb stems; as opposed to this, in Modern Spanish only one of these stems is found. These forms are the result of the medieval Spanish speakers’ intent to avoid the “inconvenient” secondary consonantal groups /-n’r-/ and /-l’r-/ that had emerged as the consequence of syncope. Four different verb stems were e. g. in the case of the verb venir: (1) there is no change, so the secondary consonantal group is not dissolved (venré); (2) assimilation occurred, the /n/ assimilated to the /r/ (verré); (3) metathesis was produced, which means that the two sounds (verné); (4) there is an epenthesis, between the /n/ or the /l/ and the /r/ inserts a phoneme (vendré). The former case is the sonly applied one in Modern Spanish. The article attempts to explain why only this one form is used in the case of the verbs, although there are examples of the other phenomena in other Modern Spanish words. The article also gives explanation of the formation of these words. Furthermore, all four verb stems are examined from the point of view of its syllable structure, the universal sonority hierarchy ad morphology.